The Impact of Gender on International Relations Simulations. Issue 4 (2nd October 2021) - Engel, Susan; Mayersen, Deborah; Pedersen, David; Eidenfalk, Joakim
Abstract: Model United Nations (MUN) simulations are an increasingly popular approach to teaching international relations, in both secondary and tertiary education. There is some evidence, however, that these simulations disadvantage female participants. Studies by Rosenthal et al. and Coughlin found that female students participate less in simulations than their male classmates. This may limit the value of simulations, which have otherwise been recognized as an effective active learning technique. This study investigates the impact of gender, and an intervention designed to address gender disparities in participation, on a MUN simulation conducted in a second-year undergraduate course. The study confirmed previous findings that women participate less than men, relative to their representation, and that this impacted their resulting grades. Participation was lowest on traditionally masculine topics. Furthermore, women enjoyed the simulation less than men, felt less included, and were less likely to report an increase in their confidence as negotiators following the simulation. The intervention we conducted, designed to ameliorate gender disparities in participation, was unsuccessful and may have inadvertently created a stereotype threat. This highlights that students come to the classroom with strongly gendered expectations, and that a short-term, explicit approach to addressing such expectations is insufficient.